Benefit-Cost Analysis and Trade Policies - Dasgupta, Partha; Stiglitz, Joseph E. (Journal of Political Economy, 1974)
This paper extends the theory of optimal taxation and government production to open economies. Appropriate rules for project evaluation and the determination of consumption, production, and trade taxes under a variety of restrictions (e.g., less than 100 percent profit taxes, government budget constraint, foreign exchange constraint) are derived. Among the results are (a) international prices should be used for evaluating public projects, unless there is a government budgetary constraint or there is a quota (this result does not require that tariff rates be optimally chosen); (b) no tariff should be levied on intermediates and only consumption taxes should be employed if there are 100 percent profit taxes. If profits are not taxed at 100 percent, both consumption and trade taxes should be employed.